Overheating investigation in UK social housing flats built to the Passivhaus standard. (October 2015) - Tabatabaei Sameni, Seyed Masoud; Gaterell, Mark; Montazami, Azadeh; Ahmed, Abdullahi
Abstract: Global environmental and energy concerns have led to a rapid growth in mandating the construction of more energy efficient dwellings in the UK. This is particularly true for the social housing sector which is partly founded by the government and it is expected to lead the way in this respect. To address this issue energy efficiency standards such as Passivhaus are increasingly adopted by both private and social housing sectors in the UK. However, data describing actual thermal performance of dwellings built to such standards, particularly in dense social housing flats, are scarce. This study considers the overheating risk during the cooling season in social housing flats built to the Passivhaus standard in the UK. It considers 25 flats over three cooling seasons in Coventry, UK. Overheating assessment based on Passivhaus criteria, using a fixed benchmark, suggests there is a significant risk of summer overheating with more than two-thirds of flats exceeding the benchmark. While the level of overheating in different flats varies considerably, detailed analysis indicates that this is more related to occupant behaviour than construction. An alternative approach to evaluating overheating risk is the adaptive thermal comfort model, which takes into account occupant vulnerability and actual outdoor temperature. Use of the adaptive benchmark suggests this overheating risk is lower for normal occupants; but higher for vulnerable occupants. These results not only have implications for the evaluation of overheating risk but also for the way in which social housing landlords place tenants of differing vulnerabilities. Highlights: Overheating risk is more related to occupant behaviour in Passivhaus (PH) flats. There is a significant risk of summer overheating based on PH benchmark. Adaptive model is better in representing the overheating risk in PH flats. Based on above model risk of overheating is higher for vulnerable occupants.